The wheel of microbiome rises, and it falls - Joanna Kołodziej; Paulina Krzemińska (Nicolaus Copernicus University in Toruń, 2024)
Intoduction: The gut microbiome plays a significant role in maintaining gastrointestinal health. Microbiota therapies involving fecal product transplantation from healthy donors, for patients with mild to moderate forms have shown significant potential to induce improvement and remission in patients suffering from inflammatory bowel disease and Clostridioides difficileinfection. There is growing interest in modulating the gut microbiome with probiotics, prebiotics and microbiota products. The undergoing rapid development over the past decade, while it is encountering some regulations related to the safety use of this method. The following paper describes and analyzes the conclusions that can be drawn from research on microbiota therapies. Methods: The review was based on the analysis of materials collected in the "Pubmed", "Google Scholar", "ResearchGate", using the mentioned below keywords. State of knowledge: Disorders of the intestinal microflora, have serious consequences in the functioning of the gastrointestinal tract and the intestinal barrier, which in turn can lead to metabolic disorders, autoimmune or neurological diseases. Therefore, from the point of view of physicians, it is crucial to learn new methods of identifying the intestinal microflora in each person and to learn techniques for its restoration. Summary: Therefore, from the point of view of physicians of various specialties, it is so important to learn new methods of identifying the intestinal microflora in each person and to learn techniques for its restoration, which can be the basis for treatment or support of the main therapy of many diseases. For many patients who do not respond sufficiently to the therapies used so far, they are the hope for improving therapeutic options, used combination with immunomodulatory drugs to raise the ceiling of their efficacy or as complementary treatment.